Uses and limits of the Equivalent Frame Model on existing unreinforced masonry buildings for assessing their seismic risk: A review. (March 2017) - Quagliarini, E.; Maracchini, G.; Clementi, F.
Abstract: Since the late 1970s, nonlinear static analysis have had an increasing use in the seismic assessment of existing unreinforced masonry (URM) buildings. Different modelling strategies can be used to evaluate the global seismic response of these buildings, such as the Continuous Constitutive Laws Model (CCLM) and the Equivalent Frame Model (EFM). Despite the CCLM modelling approach seems to be the most suitable at this aim, it needs many input data, which are often quite difficult to be known, and requires a high computational effort. For this reason, the EFM, which is based on strongly simplified hypotheses, is preferred in professional practice, where a small computational burden and a time- and cost-saving structural analysis by using few mechanical parameters is needed. In this paper, a review of its uses and limits is proposed, in order to identify the most critical issues and define its proper use in professional practice when applied to existing URM buildings. As a result, it is highlighted that the EFM can be reasonably used as a first conservative approach for the seismic assessment of existing URM buildings with box behaviour and quite regular opening patterns. Thus, up to now, from this review its use is encouraged in seismic analysis of existing URM buildings after providing them a reduction of their floors and roofs deformability, an adequate wall-to-floor and wall-to-roof connections and a regularization of the opening patterns. Highlights: Historic masonry buildings are currently modelled through the Equivalent Frame Method in professional practice. It is based on strongly simplified hypotheses so as to permit a time- and cost-saving structural analysis. This can lead to under or over conservative results. The potentiality of this method to give good approximate predictions are so presented. Critical issues and limits are also underlined.